PENERAPAN PENCATATAN AKUNTANSI TERHADAP USAHA MIKRO KECIL DAN MENENGAH (UMKM) PADATOKO CAS AUDIO - Chika Suci Ramadhita; Komala Sari, Apriliantina, Athia Rahma, Adzra Lintang Inayah, Sinta Tiara Budi (Prosiding Seminar Nasional Indonesia, 2024)
Independent productive businesses, which are usually called MSMEs, are businesses that are owned by individuals or business entities. MSMEs play an important role in the development of the Indonesian economy, but often face challenges in financial management and accounting records. This study investigates accounting record- keeping practices in MSMEs and focuses on the CAS Audio Store in Jakarta. The analytical method used is a qualitative descriptive method, through a case study approach and interview analysistechniques, this research seeks to find out how MSME accounting records are implemented atthe CAS Audio Store and explore the impact of accounting records practices on operational efficiency and financial performance. In addition, this study also evaluated the accounting software used, specifically Bee Accounting. The results show that CAS Audio has evolved frommanual record-keeping to the use of Excel and finally to paid accounting software such as Bee Accounting, strengthening their financial foundation for sustainable growth. This research provides valuable insights for other MSMEs to improve their accounting record-keeping and financial management practices.